Preparedness Of Hospitals Emergency Departments In Malaysia For Managing Acute Poisoning Cases - Alsohaim, Sulaiman Ibrahim Ali (2010)
This study was undertaken to examine the level of preparedness of accident and emergency departments across all regions in Malaysia with respect to poisoning investigational and management facilities, availability and use of treatment guidelines and other toxicological sources, training of staff and the extent by which essential treatment facilities outside the accident and emergency department are made accessible. A self-administered semi-structured questionnaire was validated and sent to all government accident and emergency departments in Malaysia and university hospitals. to comprise of 4 main sections; (a) epidemiology data, (b) availability of diagnostic and monitoring equipments, (c) treatment facilities available at the accident and emergency department and (d) toxicological information and training of staff. Collected data was analysed in SPSS version 16 using descriptive and comparative analyses.